2020
DOI: 10.1002/wrna.1626
|View full text |Cite
|
Sign up to set email alerts
|

RNA structures in alternative splicing and back‐splicing

Abstract: Alternative splicing greatly expands the transcriptomic and proteomic diversities related to physiological and developmental processes in higher eukaryotes. Splicing of long noncoding RNAs, and back-and trans-splicing further expanded the regulatory repertoire of alternative splicing. RNA structures were shown to play an important role in regulating alternative splicing and backsplicing. Application of novel sequencing technologies made it possible to identify genome-wide RNA structures and interaction network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 329 publications
(474 reference statements)
1
36
0
1
Order By: Relevance
“…In contrast, biased splicing seems not to be economical for neurite selfavoidance, because highly biased splicing heavily limits access to the full diversity from a pool of Dscam1 isoforms (Forbes et al, 2011;Hattori et al, 2009). Although recent studies suggested that biased isoform expression may be combinatorially regulated by the strength of base pairing between the docking site and selector sequence, the strength of the splice sites, and RNAbinding proteins (Anastassiou et al, 2006;Graveley, 2005;Hong et al, 2020;Ivanov and Pervouchine, 2018;May et al, 2011;Olson et al, 2007;Smith, 2005;Wang et al, 2012;Xu et al, 2019Xu et al, , 2020Yang et al, 2011;Yue et al, 2016b), the physiological significance of the highly specific bias in isoform expression remains entirely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, biased splicing seems not to be economical for neurite selfavoidance, because highly biased splicing heavily limits access to the full diversity from a pool of Dscam1 isoforms (Forbes et al, 2011;Hattori et al, 2009). Although recent studies suggested that biased isoform expression may be combinatorially regulated by the strength of base pairing between the docking site and selector sequence, the strength of the splice sites, and RNAbinding proteins (Anastassiou et al, 2006;Graveley, 2005;Hong et al, 2020;Ivanov and Pervouchine, 2018;May et al, 2011;Olson et al, 2007;Smith, 2005;Wang et al, 2012;Xu et al, 2019Xu et al, , 2020Yang et al, 2011;Yue et al, 2016b), the physiological significance of the highly specific bias in isoform expression remains entirely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible that Anti-N1 could trigger structural rearrangements in pre-mRNA. The role of an RNA structure in pre-mRNA splicing regulation is a growing area of interest [40,[108][109][110][111], and an ASO-based approach has been employed to abrogate structural elements critical for splicing control [39,112]. Off-target sites of Anti-N1 are expected to be randomly distributed throughout pre-mRNAs with their high prevalence in introns due to their (introns') large size.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative splicing (AS), an important regulatory mechanism of biological process, can generate more than one transcripts including mRNA, and lncRNA [24,43] in eukaryotes by using different splice sites. There were ve fundamental groups categorized from AS events, including intron retention (IR), exon skipping (ES), alternative donor (AD), alternative acceptor (AA) and mutually exclusive exons (MX) [44].…”
Section: Discussionmentioning
confidence: 99%